Non-native tree regeneration indicates regional and national risks from current invasions - Potter, Kevin M.; Riitters, Kurt H.; Guo, Qinfeng (Frontiers in Forests and Global Change, 2022)
Non-native (introduced, exotic, alien) species alter forest ecosystem processes, cause landscape change, interfere with services provided by native trees, and contribute to biotic homogenization. To quantify the degree of invasion by non-native trees in the United States, we combined two broad-scale datasets: (1) tree species occurrence data from the national Forest Inventory and Analysis (FIA) plot network and (2) ecoregions characterized by relatively homogeneous environmental conditions. Using the FIA statistical design, we created an indicator of non-native tree regeneration success by estimating the proportion of small trees (seedlings and saplings) relative to all trees for non-native species in the conterminous United States and southeast Alaska, Hawaii, and Puerto Rico. Species with at least 75 percent of their stems consisting of smaller stems were classified as highly invasive while those with 60 percent to 75 percent of smaller stems were classified as moderately invasive. Above these thresholds, non-native species are of ecological concern because they are established and reproducing successfully and therefore likely to continue to spread in the future. For the conterminous United States and southeast Alaska, we identified 16 highly invasive and four moderately invasive non-native tree species. Widespread highly invasive and relatively well-established species included Ailanthus altissima, Triadica sebifera, and Ulmus pumila. The richness of highly invasive species was the highest in parts of the Midwest and Mid-Atlantic States, followed by much of the Southeast. In Hawaii, we identified seven highly invasive and three moderately invasive non-native tree species. The most widespread highly invasive and well-established tree species in the archipelago were Psidium cattleyanum, Psidium guajava, Ardisia elliptica, and Syzygium cumini. The largest numbers of highly invasive species were inventoried in the lowland/leeward dry and mesic forests of O’ahu and the lowland wet and mesic forests of Hawai’i Island. Puerto Rico had 17 highly invasive and two moderately invasive tree species. The most widespread and well-established non-native species were Leucaena leucocephala, Spathodea campanulata, Coffea arabica, Syzygium jambos, and Melicoccus bijugatus. The results of this assessment offer insights into which species are most likely to alter forest ecosystems and which forests may be effectively managed to control invasive trees.